Question-declaration coupling in a university meeting talk: Discourse of social inequality and collegiality - Leonardo O. Munalim; Cecilia F. Genuino; Betty E. Tuttle (Studies in English Language and Education, 2022)
Conversation Analysis (CA) deals with the description of the microscopic and corpus-driven data in an ‘unmotivating looking’ analytical fashion. As long as there are new, interesting, or deviant features from the data, they are always worthy of a micro analysis. For this paper, we report the ‘question-declaration coupling’ in meeting talks as a new feature and explicate it through the discourse of social inequality and collegiality in the academe. The data came from a total of five recorded meetings from three departments, such as Education, Arts Science, and Social Work, in a private university in Manila, Philippines. The meetings lasted for five hours and 50 minutes. From adjacency pairs of question-answer, the sequential pattern shows that the questions deserve conspicuous answers from the subordinates, but the Chair automatically couples them with declarative sentences and other utterances that serve as continuers. The pattern is categorised as a strategic turn-suppressing mechanism to hold back the members from possibly challenging the existing policies of the institution. It is also seen as a strategic mechanism to deprive the members of extending the litanies of possible counter-arguments. From a positive perspective, we argue that it is through the air of social inequality and collegiality that people are able to know their boundaries in an ongoing interaction. Toward the end, we state the implications of the results for teaching and learning socio-pragmalinguistics. We also recommend future cross-linguistic comparisons for these microscopic features under study, considering the small corpus of this study.